Low level of ochratoxin A affects genome-wide expression in kidney of pig. (15th September 2017) - Marin, Daniela Eliza; Braicu, Cornelia; Gras, Mihai Alexandru; Pistol, Gina Cecilia; Petric, Roxana Cojocneanu; Berindan Neagoe, Ioana; Palade, Mihai; Taranu, Ionelia
Abstract: Ochratoxin A (OTA) is a mycotoxin produced by fungus belonging to Aspergillus and Penicillium genra. The aim of the present paper was to investigate if a low concentration OTA has toxic effect in pigs. Twelve piglets were fed with a control or an OTA (0.05 mg/kg feed) contaminated diet. After 30 days, animals were slaughtered and samples of blood and kidney were used for further analyses. The mycotoxin analyses showed a significant higher (6.25 times) concentration of OTA in the kidney of OTA intoxicated piglets than in control ones. While OTA has no effect on the urea and creatinine concentration, the microarray analysis of the effect of OTA on genome wide expression in the kidney of intoxicated piglets, revealed that approximately 105 different transcripts were significantly altered. As shown by the microarray results, 0.05 mg/kg of OTA can principally interfere with: i) canonical pathways (CD28 Signaling in T Helper Cells, Role of NFAT in Regulation of the Immune Response, Relaxin Signaling, IL-1 Signaling) ii) molecular and cellular function (cellular movement cellular function and maintenance, cellular growth and proliferation cellular assembly and organization, cell death and survival) etc. However, alteration of renal and urological system development and function and renal necrosis predicted through Ingenuity Pathway Analysis (IPA) were not supported by clinical pathological data. In conclusion, OTA toxicity was found even at low concentration of toxin, correlated with the activation of immune response pathways, oxidative stress response and early carcinogenic events. This effect need to be further investigated and analyzed in the context of human health. Highlights: A concentration of OTA 6.25 times higher than in control animals was found in the kidney of intoxicated piglets. Intoxication with low dose of OTA has no effect on the urea and creatinine concentration in plasma of pigs. 0.05 mg/kg of OTA can interfere with some canonical pathways and molecular and cellular function. OTA can also activate the immune and oxidative stress response as well as the early carcinogenic events.